Exercise rehabilitation for patients undergoing interventional treatment for heart valve disease: a scoping review and evidence summary - Rongxiang Zhang; Xiaoyan Lan; Pingping Huang; Yu Zhang; Chenyang Zhu; Feng Tian; Shiqi Chen; Yuan Chen (BMC Nursing)
Abstract Background This study aimed to identify, evaluate, and summarize the best available evidence on exercise rehabilitation for patients undergoing interventional treatment for heart valve disease, with the goal of informing clinical nursing practice and supporting evidence-based decision-making. Methods This scoping review was conducted in accordance with the PRISMA-ScR reporting guidelines and the Joanna Briggs Institute (JBI) framework for scoping reviews. A systematic search was performed across multiple databases and websites, including BMJ Best Practice, UpToDate, Cochrane Library, PubMed, EMBASE, CINAHL, China National Knowledge Infrastructure (CNKI), Wanfang Data Knowledge Service Platform, VIP Database, and China Medical Pulse Clinical Guidelines Network, to gather evidence on exercise rehabilitation for patients undergoing interventional treatment for heart valve disease. The search covered publications up to July 13, 2024. Researchers assessed the quality of the included literature using appropriate critical appraisal tools tailored to different types of evidence, extracted relevant content, and categorized the findings according to a pre-established evidence grading system. Results Following a strict literature screening strategy, a total of 24 studies were included, consisting of 2 clinical decision articles, 1 guideline, 6 systematic reviews, 4 evidence summaries, 7 expert consensus reports, and 4 randomized controlled trials. A total of 27 evidence items were summarized and categorized into seven dimensions: team formation, exercise rehabilitation principles, assessment, preoperative prehabilitation, postoperative exercise rehabilitation, Outpatient and home-based rehabilitation, and health education. Conclusion This study consolidated 27 pieces of evidence on exercise rehabilitation for patients undergoing interventional therapy for heart valve disease based on the principles of evidence-based care. However, the evidence has not been implemented in clinical practice and its clinical effectiveness remains to be validated.